2021
DOI: 10.1007/s10549-021-06336-y
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen-regulated protein SLC39A6: a biomarker of good prognosis in luminal breast cancer

Abstract: Purpose The outcome of the luminal oestrogen receptor-positive (ER +) subtype of breast cancer (BC) is highly variable and patient stratification needs to be refined. We assessed the prognostic significance of oestrogen-regulated solute carrier family 39 member 6 (SLC39A6) in BC, with emphasis on ER + tumours. Materials and methods SLC39A6 mRNA expression and copy number alterations were assessed using the METABRIC cohort (n = 1980). SLC39A6 protein expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…Finally, several authors have studied the relationship among some survival markers discovered in this research and breast cancer. In particular, AGR3 ( Garczyk et al , 2015 ), CA12 ( Li et al , 2019 ), CCDC170 (C6orf97; Yamamoto-Ibusuki et al , 2015 ), NDPKC (NME3; Wu et al , 2020 ), PEPT2 (SLC15A2; El Ansari et al , 2018 ), SUSD3 ( Zhao et al , 2016 ) and ZIP6 (SLC39A6; Althobiti et al , 2021 ) have been linked to breast cancer in different studies and several of these genes have also been reported to interact or be associated with ER expression and function. Furthermore, as can be seen from the included references, several of these genes have been correlated with patient survival and prognosis in breast cancer studies.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, several authors have studied the relationship among some survival markers discovered in this research and breast cancer. In particular, AGR3 ( Garczyk et al , 2015 ), CA12 ( Li et al , 2019 ), CCDC170 (C6orf97; Yamamoto-Ibusuki et al , 2015 ), NDPKC (NME3; Wu et al , 2020 ), PEPT2 (SLC15A2; El Ansari et al , 2018 ), SUSD3 ( Zhao et al , 2016 ) and ZIP6 (SLC39A6; Althobiti et al , 2021 ) have been linked to breast cancer in different studies and several of these genes have also been reported to interact or be associated with ER expression and function. Furthermore, as can be seen from the included references, several of these genes have been correlated with patient survival and prognosis in breast cancer studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, no multivariate analysis was performed. A study by Althobiti et al [ 22 ] assessed LIV1 mRNA expression and copy-number alterations using the METABRIC cohort ( n = 1980) as well as immunohistochemistry in a large ( n = 670) and annotated series of early-stage (I–III) operable BC. High LIV1 mRNA was associated with ER-positivity, low grade, good Nottingham prognostic index (NPI), older age, and luminal A subtype.…”
Section: Discussionmentioning
confidence: 99%
“…In BC, a preclinical study showed the promoter effect of LIV1 on epithelio–mesenchymal transition [ 19 ]. A few studies are available regarding the assessment of its mRNA and/or protein expression in clinical samples and analysis of correlations with clinicopathological variables [ 20 , 21 , 22 , 23 ]. Overall, they highlight the potential favorable prognostic value of LIV1 expression in early-stage BC, but none of them presented analyses per molecular subtype, nor explored the predictive value for response to chemotherapy or vulnerability/actionability to current or future systemic therapies of BC.…”
Section: Introductionmentioning
confidence: 99%
“…SLC39A6 can also be used as an indicator for early diagnosis of esophageal cancer ( 49 ). However, in luminal breast cancer, the Oestrogen-regulated protein SLC39A6 acts as a benign prognostic indicator ( 50 ). One study reported that transmembrane protein 117 (TMEM117) was associated with endoplasmic reticulum stress-mediated mitochondrial-mediated cell death ( 51 ).…”
Section: Discussionmentioning
confidence: 99%